Effects of students’ perception of teachers’ ethnic-racial socialization on students’ ethnic identity and mental health in rural China’s schools - Lai, Angel Hor Yan; Lam, Jason K. H.; Yao, Hong; Tsui, Elaine; Leung, Cynthia (Frontiers in Psychology, 2024)
Introduction Using students in the Liangshan Yi autonomous prefectures of southwestern China (n = 585; 13–15 years old), we examined (i) the effects of students’ perception of their teachers’ ethnic-racial socialization on their ethnic identity and mental health outcomes of depressive and stress symptoms; (ii) the effects of students’ ethnic identity on their depressive and stress symptoms; (iii) the differential associations among these factors in Yi ethnic minority versus Han cultural majority students. Methods We conducted a cross-sectional survey and used multistage sampling to collect the information. Chinese-validated standardized measures were used: the Patient Health Questionaires-9, Children’s Revised Impact of Event Scale-8, Multigroup Ethnic Identity Measure, Cultural Socialization Scale, and Teachers’ Attitude on Adoption of Cultural Diversity Scale. Multigroup confirmatory factor analysis and multigroup structural equation modeling were employed. Results Comparing the findings in Yi and Han students, their perception of teachers’ ethnic-racial socialization had dissimilar effects on their ethnic identity and mental health outcomes. Three key findings comparing the differences between Yi and Han students were as follows: (i) students’ perception of their teachers’ multicultural socialization practices positively affected the ethnic identity of both Yi and Han young people; however, their perception of their teachers’ socializing them to their own cultures did not exert any effect; (ii) students’ perception of teachers’ multicultural socialization practices had different mental health effects on Yi versus Han students; and (iii) ethnic identity affected the mental health of Yi ethnic minority students only. Conclusion The findings underscore the importance of teachers’ multicultural socialization in the ethnic identity development of both Yi ethnic minority and Han majority students. Ethnic identity serves as a linking variable bridging perceived teachers’ multicultural socialization practices and mental health in Yi ethnic minority students but not among the Han cultural majority youths. Research, practice, and policy implications relevant to the global context are also discussed.